Mediating Design Tensions in AI-enhanced UX: A Human-centered Framework for Enterprise Information Systems - Suranto, Beni; Cajander, Asa; Lal, Ramesh (Elsevier BV, 2026)
Integrating artificial intelligence (AI) into enterprise information systems (EIS) transforms user experience (UX) collaboration but introduces complex design tensions. This study develops the HCAI-CUX framework to address tensions related to bias, transparency, stakeholder alignment, and automation. Drawing on a structured scoping review and thematic synthesis, six key tensions were identified and mapped to five Human-Centered AI (HCAI) principles. The resulting framework offers actionable guidance for aligning ethical values with AI-enhanced UX practices in enterprise settings, contributing to more inclusive, trustworthy, and scalable design outcomes.
Keywords: 46 Information and Computing Sciences; 4608 Human-Centred Computing; 4609 Information Systems; Health Disparities; Machine Learning and Artificial Intelligence; Health Disparities and Racial or Ethnic Minority Health Research; Bioengineering; Networking and Information Technology R&D (NITRD); 3 Good Health and Well Being; 08 Information and Computing Sciences; 10 Technology; 46 Information and computing sciences; Human-Centered AI; Enterprise Information Systems; Design Tension; UX Design